Youth and Adolescent Athlete Musculoskeletal Health: Dietary and Nutritional Strategies to Optimise Injury Prevention and Support Recovery - Rebekah Alcock; Matthew Hislop; Helen Anna Vidgen; Ben Desbrow (Journal of Functional Morphology and Kinesiology)
Background: Despite the well-documented benefits of exercise and sports participation, young athletes are particularly vulnerable to musculoskeletal injuries. This is especially true during periods of rapid growth, sports specialisation, and high training loads. While injuries are an inevitable aspect of sports participation, the risk can be minimised by promoting the development of strong, resilient tissues through proper nutrition and injury prevention strategies. Moreover, targeted nutrition strategies can accelerate recovery and rehabilitation, allowing for a quicker return to sports participation. Methods: This narrative review synthesises scientific evidence with practical insights to offer comprehensive dietary recommendations aimed at strengthening tissues and supporting the healing process during recovery and rehabilitation. The selection of all sources cited and synthesised in this narrative review were agreed upon by contributing author consensus, experts in sports nutrition (R.A., H.V., B.D.) and exercise and sports medicine (M.H.). Results: Key topics include factors that contribute to injury susceptibility, general dietary recommendations for growth and development, sports nutrition guidelines, and nutrition considerations during injury and rehabilitation. This review also addresses external factors that may lead to suboptimal nutrition, such as food literacy and eating disorders. Conclusions: By highlighting these factors, this article aims to equip coaches, nutritionists, dietitians, athletic trainers, physical therapists, parents/guardians, sporting organisations, and schools with essential knowledge to implement effective nutritional strategies for injury prevention, recovery, and rehabilitation, ultimately enhancing long-term health and athletic performance.